Grammatical Cohesion Devices of Hortatory Exposition Texts Used on Senior High School Textbook: A Critical Pedagogy Analysis - Sarah Nadia Nirmala Putri; Andi Rustandi; Misbahudin Misbahudin (Jurnal Siliwangi: Seri Pendidikan, 2018)
This research identifies the grammatical cohesion devices of hortatory exposition texts used on senior high school textbook. A descriptive qualitative method was employed in conducting the study. It was aimed to find out (1) types of grammatical cohesion devices realized on hortatory exposition texts of senior high school textbook, (2) the extent to which grammatical cohesion devices help the texts achieve their cohesion, (3) the pedagogical benefits of hortatory exposition texts taken from senior high school textbook after being analyzed by grammatical cohesion devices viewed from the critical pedagogy philosophies. There are five hortatory exposition texts that were analyzed by using the cohesion taxonomy as suggested by Halliday Hasan (1976). The findings revealed that the total use of grammatical cohesion devices in five hortatory exposition texts were different. The first text showed the small use of reference, substitution, ellipsis, and conjunction, it was counted 39 items found in the first text. Meanwhile the use of grammatical cohesion devices in the third text was the highest, it was counted 148. Moreover, it was also proved that those devices could helped the text achieved their cohesion. The writer also summed up that hortatory exposition texts from textbook were beneficial for the students and it was appropriate with critical pedagogy principles.